Competitividad en las MIPYMES del sector comercio de la ciudad de Latacunga. - Chicaiza Caiza, María Eugenia (2020)
The purpose of this research was to determine the levels of competitiveness of MSMEs in the commercial sector in Latacunga city, so based on the methodology proposed by the map of the Inter-American Development Bank (IDB), an instrument adapted to a sample of 95 businesses was applied, considering a population of 5,924 establishments (INEC, 2017). The instrument consisted of two sections, the first associated with seven general questions, and a second section related to competitiveness, composed of fifty approaches that were rated on a Likert scale from 1 to 5, where 1 represents never or not, 2 little, 3 regular, 4 good and 5 excellent or quite. Cronbach's Alpha was used to statistically validate the questionnaire, whose result allows the researchers to accept the validity and internal coherence of the instrument. Additionally, hypothesis testing was performed to identify possible differences in results considering legal personality and the category of a familiar business or non-familiar one. The study was complemented with the estimation of factor analysis to extract the dimensions corresponding to the data collected. The results allow the researchers to conclude that the general competitiveness of the businesses in the commerce sector in Latacunga city has an average of 3.96, which corresponds to the range of good; regarding the dimensions that were evaluated as strategic planning with 3.2511; operations with 4,0459; Quality assurance 4.3536; commercialization 3,9695; accounting and finance 4,4131; 3,7175 human talent and 3,9578 environmental management. Statistically, only significant differences could be identified in the strategic planning dimension for businesses with legal personality, whose value is superior to those that are natural persons. Finally, the factor analysis allowed grouping the data into seven factors that can be considered as marketing and sales, compliance with regulations of various kinds, activity planning, business accounts, the necessary innovation, concern for the environment, and fidelity of the consumer.